POTENTIAL FOR ECOTOURISM DEVELOPMENT IN THE FOREST AREA OF BOJONEGORO REGENCY AS SUSTAINABLE TOURISM - Wijoyo, Handoko Sosro Hadi; Mustofa, Moh; Anam, Moh Saiful (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
There are many ways to save the forest, one of which is to make theconcept of ecotourism in forest areas, both natural and socio-culturalecotourism which is the local wisdom of residents. Local wisdom itself isthe life of the village community which is one of the attractions of touristsfrom urban areas who have never felt village life, especially forest areas,or tourists who want to get peace in the village. In addition, the culturethat is currently still believed by the forest community and has theopportunity to become a potential as a cultural heritage of thecommunity. Ecotourism conceptualized is a form of tourism that leadsto meta tourism. Ecotourism that not only sells destinations but sellsphilosophy. From this aspect, ecotourism will not recognize marketsaturation, the results of observations show that the forest area that hasthe potential to create Ecotourism is between two districts, namely SekarDistrict and Gondang District which are located in Sambongrejo,Krondonan, Klino and Deling Villages.